2020
DOI: 10.3389/fcimb.2020.00336
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Skin Microbiota Imbalance and Responses to Clinical Treatment in Children With Atopic Dermatitis

Abstract: Background: Atopic dermatitis (AD) is a common cutaneous disease, associated with imbalances in the skin microbiota. Objective: To explore the characteristics of the cutaneous microbiota and its dynamic changes during clinical treatment. Methods: Cutaneous swab samples were collected from 51 AD patients before treatment, and 40 AD patients remained after a 2-week treatment with mometasone and mupirocin. Results: AD patients exhibited significant enrichments of Prevotella and Desulfovibrio as well as obvious re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 46 publications
0
16
0
1
Order By: Relevance
“…Enrichment of Lachnospiraceae and Clostridiales has been reported under ultraviolet-B radiation exposure (17), while Moraxellaceae have been found to contribute to mucosal inflammation (18). In a previous study, significant enrichment of Prevotella was observed in the skin microbiota in patients with atopic dermatitis (19). Zhang et al reported Lactococcus garvieae to be a potential pathogenic cause of skin ulceration syndrome outbreak (20).…”
Section: Discussionmentioning
confidence: 99%
“…Enrichment of Lachnospiraceae and Clostridiales has been reported under ultraviolet-B radiation exposure (17), while Moraxellaceae have been found to contribute to mucosal inflammation (18). In a previous study, significant enrichment of Prevotella was observed in the skin microbiota in patients with atopic dermatitis (19). Zhang et al reported Lactococcus garvieae to be a potential pathogenic cause of skin ulceration syndrome outbreak (20).…”
Section: Discussionmentioning
confidence: 99%
“…9 However, the impact of treatment on skin microbiota among patients with AD remained unclear and the results remained controversial across studies. [12][13][14][15] Therefore, it is warranted to summarise the available studies to understand the role of skin microbiota in the treatment and prognosis of AD. We will systematically review studies focusing on the effect of treatments on skin microbiota among patients with AD, including topical therapy, phototherapy, systemic treatment, etc.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with AD with specific characters, the abovementioned changes were not observed in patients after treatment; such phenomena may be associated with low abundance of S. aureus in these patients. 15 Additionally, to the best of our knowledge, there is no systematic review to evaluate the effect of treatments on skin microbiota in patients with AD. It is, therefore, warranted to summarise the available studies for understanding the role of skin microbiota in the treatment and prognosis of AD.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding WHO region, the majority of studies were conducted in the European Region (n = 50, 55%), followed by the Western Pacific Region (n = 21, 23%), the Region of the Americas (n = 16, 18%) and the African Region and the Eastern Mediterranean Region (both n = 1, 1%). Investigated characteristics included the following categories: skin barrier function (n = 15), [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] serum blood cell types and markers (n = 23), 9,18,23,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] serum Ig levels and sensitization (n = 15), 20,22,25,51,54-64 microbial colonization (n = 10), 15,[65][66][67][68][69][70][71][72][73] DNA mutations (n = 14), 10,51,…”
Section: Phenotypes Based On Disease Severity (Phenotype Group 1)mentioning
confidence: 99%